Comparing Physics Textbooks in Terms of Assessment and Evaluation Tools - Zeynep Başkan Takaoğlu (International Journal of Assessment Tools in Education)
Assessment and evaluation instruments provide teachers the opportunity of shaping education in the beginning, contributing to education during the process and evaluating education at the end of the process. Textbooks, on the other hand, are resources that present the aforementioned contributions to teachers at first hand. Thus, the study aims to compare the distribution of assessment and evaluation instruments in the physics textbooks being used in the academic year of 2011- 2012 and 2016-2017 according to units, settlement within units and types of assessment instruments that are used. For that purpose, 9, 10, 11 and 12th grade textbooks being used in physics lessons in the academic year of 2011-2012 and 2016-2017 were examined via document analysis method. As a result of the study, it was determined that the highest number of assessment instruments in physics textbooks from two different years was encountered in the unit of force and motion. The reason for this unit having higher number of questions could be associated with higher number of mathematical operations in the unit intended for allowing students to overcome their mathematical deficiencies by practicing such questions. It was observed that the number of questions was increased especially in the books being used in the academic year of 2016-2017 and alternative assessment instruments were fewer than traditional assessment instruments. Traditional assessment instruments are still used very frequently in the textbooks, which proves the effect of traditional approaches in assessment and evaluation. Another reason for this condition is that a result-oriented evaluation is used in the university entrance exam. In the light of these results, it is suggested to make the university exam student-centered rather than making an arrangement in textbooks.